2015
DOI: 10.3899/jrheum.140517
|View full text |Cite
|
Sign up to set email alerts
|

Falls Associated with Muscle Strength in Patients with Knee Osteoarthritis and Self-reported Knee Instability

Abstract: High knee extension and flexion muscle strength decreased the risk of falls in patients with knee OA and self-reported knee instability. After considering the effect of pain, there was insufficient statistical power to detect an association between muscle strength and falls, which might be because of the low number of subjects who fell (n = 31).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 44 publications
1
76
0
Order By: Relevance
“…Musculoskeletal pain in this population has been linked to falls (Asai et al, 2015;de Zwart et al, 2015;Kitayuguchi et al, 2015), and the The F-statistics and corresponding P-values of Local Divergence Exponent (LDE), Root Mean Square (RMS) and magnitude of the stride-to-stride variability (SDs) from thorax movements (velocity) are reported for the anteroposterior (AP), mediolateral (ML) and vertical (VT) axes and post-hocs with Bonferroni correction for low back pain (LBP), washout (wo) LBP, calf pain (CalfP) and wo CalfP. Note that no post-hoc was performed on the significant RMS condition  speed interaction as the effect of the condition  axis interaction was greater.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Musculoskeletal pain in this population has been linked to falls (Asai et al, 2015;de Zwart et al, 2015;Kitayuguchi et al, 2015), and the The F-statistics and corresponding P-values of Local Divergence Exponent (LDE), Root Mean Square (RMS) and magnitude of the stride-to-stride variability (SDs) from thorax movements (velocity) are reported for the anteroposterior (AP), mediolateral (ML) and vertical (VT) axes and post-hocs with Bonferroni correction for low back pain (LBP), washout (wo) LBP, calf pain (CalfP) and wo CalfP. Note that no post-hoc was performed on the significant RMS condition  speed interaction as the effect of the condition  axis interaction was greater.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of impaired sensorimotor control, reduced gait stability is associated with aging (Kang and Dingwell, 2008) and neurological disorders (Ijmker and Lamoth, 2012;Reynard et al, 2014). Musculoskeletal pain has been associated with fall risk (Asai et al, 2015;de Zwart et al, 2015;Kitayuguchi et al, 2015) and may also impact stability. For example, spinal movement stability was lower during pain than no pain (Ross et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Eight (73%) studies reported a definition of a fall . However, the fall definition was inconsistent across the studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, the fall definition was inconsistent across the studies. Some used recommended guidelines or a broad definition of a fall; others used a specific definition . There was also variation in the methods used to collect a falls history.…”
Section: Resultsmentioning
confidence: 99%
“…A study by van den Hoorn, Hug, Hodges, Bruijn, and van Dieën (2015) investigated if nociceptive stimulation and induced pain affect gait stability. Previous research suggests that musculoskeletal pain is associated with fall risk and has a negative impact on stability (Asai, Misu, Sawa, Doi, & Yamada, 2015;de Zwart et al, 2015;Kitayuguchi, Kamada, Okada, Kamioka, & Mutoh, 2015;Ross, Mavor, Brown, & Graham, 2015).…”
Section: Discussionmentioning
confidence: 99%